The Effect of Information Technology Based Learning Models on Junior High School Students' Learning Outcomes and Motivation - Hidayat, Teggy; Alfayed, Gio; Arlin, Dzakirah Hafizah; Nur Ja’a, Ainun; Andikos, Adi Fitra (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
Information technology (IT)-based learning models can help students obtain information quickly and accurately. This research aims to analyze the influence of IT-based learning models on junior high school students' learning outcomes. The research design used was an experiment with two groups, namely an experimental class that used an IT-based learning model and a control class that used conventional learning methods. Data was obtained through pretests and posttests given before and after treatment. The research results showed that there were significant differences between the learning outcomes of the experimental class and the control class. In the pretest, the average experimental class score was 3.37 points higher (t = 2.484; p = 0.013). This difference increased in the posttest, with the average experimental class score being 12.16 points higher (t = 4.215; p = 0.000). These findings indicate that an attractive IT-based learning model can significantly improve student learning outcomes. It is hoped that the results of this research can be a reference for educators in adopting IT-based learning models as an effective learning strategy to improve the quality of student learning outcomes.